Fellow Traveller: A British Columbia Fisherman Writes Home from the Eastern Bloc, 1952 - Isitt, Benjamin (Labour / Le Travail, 2009)
The article focuses on the letters wrote by Elgin Neish, a member of the Labor-Progressive Party (LPP), during his seven week trip from Eastern Europe to Beijing, China in 1952. It explains that the letters offered a significant perspective of a radical British Columbia trade unionist during the Cold War as well as important global subjects. It notes that Neish traveled to Beijing to participate in the Asia and Pacific Rim Peace Conference, which reflected on the communist-led peace activism during the Cold War and the relationships between the Canadian and Chinese Communists, from October 2-12.
Keywords: BEIJING (China); CHINA; COLD War, 1945-1989; CONFERENCES & conventions; EUROPE, Eastern; Labor Unions; Labor union members; Letters; NEISH, Elgin